Foraging behavior and body temperature of heritage vs. commercial beef cows in relation to desert ambient heat. (October 2021) - Nyamuryekung'e, Shelemia; Cibils, Andres F.; Estell, Richard E.; McIntosh, Matthew; VanLeeuwen, Dawn; Steele, Caitriana; González, Alfredo L.; Spiegal, Sheri; Reyes, Leonel Avendaño; Rodríguez Almeida, Felipe A.; Anderson, Martha
Abstract: We studied foraging patterns of Raramuri Criollo (heritage breed, "RC") and Angus x Hereford (commercial beef breed, "AH") cows in relation to ambient heat and body temperature during summer (2016 and 2017) and winter (2017 and 2018) in the Chihuahuan Desert. Cows of each breed grazed separately in two adjacent pastures ( 1100 ha) in a crossover design for four weeks in each season/year. Animals were fitted with temperature loggers attached to blank CIDRs (Controlled Internal Drug Release device) devoid of hormones that recorded body temperature (BodyT), and GPS collars that recorded position and ambient temperature (CollarT). All sensor data were logged at 10 min intervals. A landscape thermal map (LandT) was developed from Landsat satellite imagery for habitat analysis using GPS locations chosen by individual collared cows, and air temperature (AirT) was recorded by a nearby weather station. Data were analyzed within four daytime segments: dawn (sunrise – 9AM); pre-noon (9AM – noon); post-noon (noon – 3PM); and dusk (3PM – sunset). ANOVA was used to determine whether BodyT, CollarT, LandT selection, or animal movement variables within each of the four daily segments differed (P < 0.05) for RC vs. AH cows. BodyT and CollarT increased as day progressed in both seasons. During summer, RC had lower BodyT and higher CollarT than AH (P < 0.05) during the hottest hours of the day. Increasing AirT throughout the day was associated with selection of cooler LandT in RC but not AH during summer. In winter, both breeds selected warmer landscape locations as the day progressed. Compared to AH, RC cows traveled farther, at higher velocities, and spent more time grazing and traveling and less time resting, with largest breed differences observed during the hottest hours of summer days. These results suggest that Raramuri Criollo cows exhibited higher thermotolerance than did AH. Elevated ambient summer temperatures in the Chihuahuan Desert appear to impose fewer constraints on heritage RC movement patterns compared to mainstream commercial AH cows. Highlights: Ranching in a hotter and drier southwestern United States will require the use of adapted cattle genetics. Raramuri Criollo (heritage breed) cows maintained lower body temperature during the hottest hours of summer afternoons. Raraumri Criollo cows either maintained or increased activity rates during hot afternoon vs. cool morning hours. Heritage cattle breeds could help ranchers adapt to hotter and drier environmental conditions.